Hydrothermal Synthesis, Crystal Structure, and Luminescent Property of a Novel Zn(II)-Organic Framework With Tetranuclear [Zn4(μ3-OH)2] Clusters Linked by an Unsymmetrical Pyridylbenzoate Ligand With Helical Chains. Issue 3 (3rd March 2016) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract : A new zinc(II)-organic framework, [Zn2 (OH)(3, 4-PBC)3 ]n (1 ), has been obtained by the reaction of Zn(NO3 )2 with an unsymmetrical pyridylbenzoate ligand, 3-pyrid-4-ylbenzoic acid (3, 4-PBC). Single-crystal X-ray diffraction studies reveals that it comprises [Zn4 (μ3 -OH)2 ] clusters linked by the unsymmetrical ligand 3, 4-PBC, forming a new metal-organic framework with helical chains. Furthermore, the luminescent property for complex 1 has been investigated.